Aqueous Extract of Winter Jasmine Leaves Mediated Biosynthesis of Silver Nanoparticles - Adaila, Kawther; Elraies, samia; omar, abdounasser; Ben Younis, Eman; Alhaj, Hiba; Shlebek, Salsabel; Ali, Sara (Scientific Journal for Faculty of Science-Sirte University, 2023)
This study reports a rapid and eco-friendly green method for the synthesis of silver nanoparticles from silver nitrate solution using winter jasmine leaves extract as a reducing agent of Ag+ to Ag0. A visible Absorption Spectrophotometer was used to monitor the formation of silver nanoparticles (AgNPs). The visible spectrum showed an absorption peak at 420 nm which reflects the surface plasmon resonance (SPR) of AgNPs. In addition to that, the synthesis of AgNPs was confirmed by the color change of the solution. By studying the most important factors affecting the formation of AgNPs, it was noted that the productivity of AgNPs in the solution increased by increasing the pH of the solution, and the basic medium was the appropriate medium for the synthesis process. Also, the amount of produced AgNPs increased with the increase in temperature, volume of extract, reaction time, the extract volume ratio of the winter jasmine leaves, and silver nitrate concentration. In conclusion, the aqueous extract of winter jasmine leaves represents a suitable material for the biosynthesis of AgNPs, and large amounts of AgNPs with appropriate sizes may be obtained by controlling the parameters that affect the synthesis process.